Salt Reduction at the Population Level - Warren, Bethany (World Bank, Washington, DC, 2022)
Excess salt intake is a widespread global problem contributing to increased blood pressure, the leading risk factor for preventable deaths worldwide. Effective and feasible interventions exist to reduce salt intake at a population level, including front-of-package labeling, industry reformulation targets, marketing restrictions, taxing salty products or subsidizing healthier substitutes, reducing salt levels in food served or sold in public institutions, and encouraging individuals to use alternatives to salt at home. Over 90 countries have implemented salt reduction initiatives; however, these have been mostly high- and upper-middle income countries. Implementing cost-effective proven salt reduction approaches can avert millions of preventable deaths, save lives and health care costs, and boost productivity and human capital.